Rural settlement as a factor of administrative and territorial changes (on the example of Zakarpattia and Chernivtsi regions) - Skliarska , O. I. (Man and Environment. Issues of Neoecology, 2022)
Purpose: to analyze the features of rural settlement in Zakarpattia and Chernivtsi regions and to identify its influence on the formation and functioning of territorial communities and districts of these regions.Methods. comparative-geographical, statistical, analytical method, structural-functional approachResults: the rural settlement network of the Zakarpattia and Chernivtsi regions was analyzed from a socio-geographic point of view, taking into account the similarity of natural and geographical conditions, historical, ethno-geographical aspects of the formation of settlements and modern socio-spatial processes in the regions. It is noted that the regions have a number of common features of rural settlement, in particular, high density and average population of settlements in the plain part and zones of dispersed settlement in mountainous areas, which must be taken into account in the process of formation of territorial communities. It is noted that according to the results of the ATU reform in the regions, rural communities absolutely prevail. This will contribute to the preservation of the demographic and socio-economic potential of rural settlements - community centers, however, in remote peripheral and depressed areas, rural communities may not be able to cope financially and administratively given the limitations of their own resources. Possible positive and negative consequences of the impact of the reform on changes in inter-settlement relations, functions of settlements, and their further development are identified and summarized.Conclusions: Intra-regional differences in rural settlement are an important factor in administrative-territorial changes and were taken into account in the process of formation of territorial communities and new districts. Most communities in both regions are rural; the settlements that became their centers received broad powers and prospects for development. In today's conditions, most rural communities cannot take advantage of the opportunities of decentralization due to the limited socio-economic potential of settlements. According to indicators of economic activity, these communities are mostly subsidized and require significant investment income. The development of rural areas will contribute to the strengthening of the grassroots link of the administrative-territorial system.